Characterization of Phenolic Compounds in Pinus laricio Needles and Their Responses to Prescribed Burnings - Cannac, Magali (Molecules, 2007)
Fire is a dominant ecological factor in Mediterranean-type ecosystems. Management strategies include prescribed (controlled) burning, which has been used in the management of several species, such as Pinus nigra ssp laricio var. Corsicana, a pine endemic to Corsica of great ecological and economic importance. The effects of prescribed burning on Pinus laricio have been little studied. The first aim of this study was to characterize total and simple phenolic compounds in Pinus laricio. The second aim was to understand: i) the short term (one to three months) and medium term (three years) effects of prescribed burning, and ii) the effects of periodic prescribed burning on the production of phenolic compounds in Pinus laricio. The first result of this study is the presence of total and simple phenolic compounds in the needles of Pinus laricio. 3-Vanillyl propanol is the major compound. After a prescribed burning, the synthesis of total phenolic compounds increases in Pinus laricio for a period of three months. Total phenolic compounds could be used as bioindicators for the short-term response of Pinus laricio needles to prescribed burning. Simple phenolic compounds do not seem to be good indicators of the impact of prescribed burning because prescribed burnings are low in intensity.